2020
DOI: 10.1177/1077695820925306
|View full text |Cite
|
Sign up to set email alerts
|

Toward a New Conceptualization of Journalistic Competency: An Analysis of U.S. Broadcasting Job Announcements

Abstract: Journalistic competency is a constitutive element of professional values and practices in journalism. But what constitutes journalistic competency in today’s ever-changing media landscape? Existing literature lacks theoretical and empirical understandings of journalistic competency, especially in broadcasting. Drawing on Cheetham and Chivers’s competence model, we examine professional competencies as defined by broadcast media through a content analysis of 359 job announcements. Four dimensions of jou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…In this context, typical journalist competences such as general competence, subject competence, process competence and professional values as suggested by Donsbach (2014) are important but appear subordinate. Guo and Volz (2020) suggest that updated core competences for the broadcast industry include technical skills, news judgment, writing, editing, shooting, and reporting. Notably, Nygren and Appelberg (2013) found that the lowest share of Swedish journalists covering a special area compared to other types of media is found in Public Service Broadcasting.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, typical journalist competences such as general competence, subject competence, process competence and professional values as suggested by Donsbach (2014) are important but appear subordinate. Guo and Volz (2020) suggest that updated core competences for the broadcast industry include technical skills, news judgment, writing, editing, shooting, and reporting. Notably, Nygren and Appelberg (2013) found that the lowest share of Swedish journalists covering a special area compared to other types of media is found in Public Service Broadcasting.…”
Section: Introductionmentioning
confidence: 99%
“…Considering this, qualifications such as strong verbal communication skills and excelling in pronunciation frequently appear in the job descriptions and qualifications for newscasters. Because broadcast journalists and practitioners have these standards for themselves (Guo and Volz 2020), audiences have been conditioned to expect them. Qabilovna (2020) analyzed audience expectations for television news anchors and identified a high level of verbal communication and "effectiveness of speech" (342) were expected by viewers.…”
Section: Delivery Mistakes and Credibilitymentioning
confidence: 99%